Novel synthetic antimicrobial peptides with In-Vivo and In-Vitro activity against Streptococcus Pneumoniae / Le Cheng Foh - Le, Cheng Foh (2013)

(untitled)
Streptococcus pneumoniae is a major human bacterial pathogen causing life threatening diseases such as meningitis, bacteremia, and pneumonia. Younger children are heavily affected by pneumococcal infections. Pneumococcal conjugate vaccines (PCVs) are serotype-specific and require data on local serotype distribution to predict the coverage of PCVs. Moreover, the escalating incidence of antibiotic resistance S. pneumoniae has prompted the development of novel antimicrobial agents. Antimicrobial peptides (AMPs) have been increasingly recognized as the new generation antibiotics due to their potent antimicrobial activity. In this study, we sought to design novel synthetic antimicrobial peptides against S. pneumoniae and determine the in vitro and in vivo activities of the peptides. A collection of 151 pneumococcal clinical isolates from University of Malaya Medical Centre, Kuala Lumpur were serotyped using multiplex PCR and the penicillin susceptibility was determined using agar dilution method. Biocomputational tools were employed to design the peptides based on the publicly available AMPs. The designed AMPs were tested for minimum inhibitory concentration, bacterial killing kinetics, and synergism activity. Broad spectrum antibacterial activity against eight common bacterial pathogens was also determined. Morphological changes of pneumococcal cells were observed using transmission electron microscopy. The designed AMPs were also assessed for hemolytic and cell cytotoxicity. In vivo therapeutic efficacy and acute toxicity of the peptides were assessed using an in-house mouse model. Serotypes 19F and 23F were the two prevailing serotypes among Malaysian population with serotype 19F significantly associated with penicillin resistance. Penicillin-nonsusceptible S. pneumoniae constituted half (50.3%) of the total isolates. and as high as 87.5% of penicillin-resistant S. pneumoniae (PRSP) were PCV7-vaccine serotypes. From the peptide designs, antimicrobial testing showed that the five hybrid iv peptides (DM1-5) exhibited strong antipneumococcal activity irrespective of penicillin susceptibility of the isolates. These isolates included the highly prevalent serotype 19F. The pneumococcal killing rates were higher than penicillin by 38 – 64%, 54 – 76%, and 30 – 57% for penicillin-resistant, intermediate, and susceptible isolates at 30 min posttreatment, respectively. The DMs and other peptides produced synergism in combination with penicillin against S. pneumoniae and displayed broad spectrum antibacterial activities. The DMs induced overwhelming cellular damages leading to cell death. Besides, DMs exhibited low hemolytic activity (HC50 >250 μg/ml) with varying degrees of cell cytotoxicity against NL20 and A549 cell lines. Notably, DM3 (40 mg/kg) given via intraperitoneal route at 12 hrs interval for three dosing regimens protected 50% of mice from lethal systemic infection by a PRSP strain. Interestingly, combination therapy using low doses (10mg/kg and 20mg/kg) DM3 and penicillin showed therapeutic synergism with 20-50% higher survival rates than the sum of the standalone treatments. Complete protection (100%) was achieved with DM3 (20 mg/kg) – penicillin (20 mg/kg) combination. Pneumococcal infections continue to affect humans and antibiotic-resistant S. pneumoniae would further complicate the treatment outcomes. The current study demonstrated that AMPs represent the promising new generation antibiotics as standalone therapeutics or in combination with conventional antibiotics. Novel designed AMPs candidates can be designed following careful designing approaches to generate peptides with high therapeutic potential to be further developed into clinically useful antibiotics.